Just in time and competitive advantage: understanding their linkages and impact on operational performance - Ramlawati, Ramlawati (Archives of Business Research, 2018)
This study aims to analyze the influence of Just in Time on competitive advantage and operational performance. This research was carried out on a manufacturing company in Makassar Industrial Area, a sample of 40 respondents consisting of marketing managers, production managers and financial managers. The results of data analysis using Partial Least Square (PLS) provide evidence that Just in Time has a significant effect on competitive advantage and operational performance